Hyperintense acute reperfusion marker associated with hemorrhagic transformation in the WAKE-UP trial. (June 2021) - Wouters, Anke; Scheldeman, Lauranne; Dupont, Patrick; Cheng, Bastian; Ebinger, Martin; Jensen, Märit; Endres, Matthias; Gerloff, Christian; Muir, Keith W; Nighoghossian, Norbert; Pedraza, Salvador; Simonsen, Claus Z; et al.
Introduction: Hyperintense acute reperfusion marker (HARM) is an indicator of early disruption of the blood-brain-barrier. Our aim was to investigate the incidence of HARM in patients with a diffusion weighted imaging (DWI) - fluid attenuated inversion recovery (FLAIR) mismatch and determine the association between this marker and hemorrhagic complications as well as clinical outcome. Patients and Methods: We included patients from the Efficacy and Safety of MRI-Based Thrombolysis in Wake-Up Stroke (WAKE-UP) trial who underwent baseline perfusion weighted imaging (PWI). HARM was defined as a hyperintense signal in the cerebrospinal fluid space on FLAIR imaging at 24 h after baseline imaging. We compared baseline characteristics in patients with and without HARM and investigated the association between HARM and any hemorrhagic transformation (HT) and parenchymal hematoma (PH) in a multivariate logistic regression. We also explored HARM as an independent predictor of poor outcome, defined as a modified Rankin Scale of 3–6 at 90 days. Results: HARM was present in 14 of 223 (6%) patients with a DWI-FLAIR mismatch and baseline characteristics were similar in patients with vs without HARM. HARM showed an independent relationship with any HT (OR 6.67; 95%CI 1.72–26.58) and any PH (OR 6.92; 95%CI 1.34–29.49). The rate of HARM was similar in patients with good and poor outcome (5%, p = 0.90). Conclusion: In the WAKE-UP trial, the incidence of HARM was only 6% at 24 h. An association was present between HARM and hemorrhagic complications, but no relationship with functional outcome was observed.